DUKUNGAN SOSIAL TEMAN SEBAYA PADA DEWASA AWAL YANG MENGALAMI QUARTER-LIFE CRISIS - Afifah, Nurul; Wihartati, Wening; Ikhrom, Ikhrom (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Quarter-life crisis is a common crisis phase experienced by early adulthood individuals, characterized by confusion about life direction, career uncertainty, social pressure, and emotional instability. One factor that is believed to be able to support individuals through this phase is social support, especially from peers. This study aims to explore the experiences of early adulthood individuals in receiving social support from peers and how this support affects the quarter-life crisis they experience. This study uses a qualitative approach with a phenomenological method. Data were obtained through in-depth online interviews with four 20-year-old participants. The results of the study showed that peer social support is present in providing attention, information, instrumental, and assessment. This support plays an important role in helping individuals manage emotions, provide new perspectives, and increase self-confidence in facing various challenges of quarter-life crisis. The results of the study confirm that the presence of peers as an emotional and social support system has a significant contribution to the adaptation process of early adulthood individuals to the dynamics of the developmental crisis they experience.